Leadership and creativity - Afshari, M.; Ayoufu, W. (2011)
Although research studies have indicated that transformational leadership style is related to creativity, relatively limited researches have attempted to determine the moderating effect of training on the relationship between transformational leadership and creativity. Data were collected from 110 postgraduate students at the Faculty of Education. In this study, Moderated Multiple Regression analysis was used to test hypothesis and theoretical model. Findings of this study indicated that training factor (untrained students vs. trained students) significantly affected the relationship between transformational leadership and creativity. It is suggested that supervisors should engage in transformational leadership behaviors in order to enhance the creative performance of their students. Also, creativity training program should be provided for students to learn creativity knowledge, attitudes, workplace idea generation and idea implementation.